The Idea of a Theatre in Sixteenth-Century China: Xu Wei’s (1521-1593) Nanci xulu - Llamas, Regina (University of Hawai‘i Press, 2005)
Xu Wei was not the first to write about theater: before him others had written about the life of actors, the authors and their works, about music and prosody, singing methods, the function and style of drama and the composition of plays. The birth of drama was already understood as a by-product of leisure, and so was its potential as a popular instrument for improving, expounding and disseminating social values.1 But Xu Wei’s essay, A Record of Southern Drama Song written in 1559, is the first and only “defense” of southern drama (nanxi) we have.2 It is also an apology that reflects and responds to current concerns with the genre and how this genre had to be understood. This paper will explore how Xu Wei attempted to establish the reputation of southern theater on the basis of contemporary values of naturalness and authenticity, and how he modified and honed these values to fit his defense. It will show that Xu’s advocacy of natural language and authentic music in Southern Drama implied standards that had long since departed the popular milieu he claimed conceived them and became instead the aesthetic values of an educated class wed to distinctive regional and ethnic alliances.
Keywords: 55 Historia::5506 Historia por especialidades::5506.13 Historia de la literatura; ODS 4 - Educación de calidad